Introduction to special issue on regional growth opportunities - Arndt, Channing; Roberts, Simon J. (Informa UK Limited, 2018)
This issue contains seven articles addressing the major changes underway in the integration of economies in southern Africa. In the first article, Channing Arndt and Simon Roberts map out the changes in trade flows, which demonstrate the extent to which South Africa’s diversified exports to Southern African Development Community (SADC) countries have grown, and provide an overall policy synthesis drawing from the articles in this issue and other sources. The spread of major supermarket chains across southern Africa is assessed in two articles. Reena Das Nair maps the growing reach of supermarkets in southern Africa; this is changing the way food is purchased, with implications throughout the marketing chain. Supermarkets enforce tight quality and timeliness requirements and can have substantial power over suppliers (as they are the route to consumers). Shingie Chisoro, Reena Das Nair and Francis Ziba evaluate supplier capabilities and point to the importance of policies to support supplier upgrading and linkages with supermarket networks to access the growing consumer markets across SADC. In contrast, failure by local suppliers to link to supermarkets implies continuous undermining of local production.